A novel probabilistic source apportionment approach: Bayesian auto-correlated matrix factorization - A. Rusanen; A. Rusanen; A. Björklund; M. I. Manousakas; J. Jiang; J. Jiang; M. T. Kulmala; M. T. Kulmala; M. T. Kulmala; K. Puolamäki; K. Puolamäki; K. R. Daellenbach (Atmospheric Measurement Techniques, 2024)
The concentrations of atmospheric particulate matter and many of its constituents are temporally auto-correlated. However, this information has not been utilized in source apportionment methods. Here, we present a Bayesian matrix factorization model (BAMF) that considers the temporal auto-correlation of the components (sources) and provides a direct error estimation. The performance of BAMF is compared with positive matrix factorization (PMF) using synthetic Time-of-Flight Aerosol Chemical Speciation Monitor data, representing different urban environments from typical European towns to megacities. We find that BAMF resolves sources with overall higher factorization performance (temporal behavior and bias) than PMF on all datasets with temporally auto-correlated components. Highly correlated components continue to be challenging and ancillary information is still required to reach good factorizations. However, we demonstrate that adding even partial prior information about the chemical composition of the components to BAMF improves the factorization. Overall, BAMF-type models are promising tools for source apportionment and merit further research.